Factors Affecting Financial Literacy In The Use Of Financial Institutions Products and Services - Ni Kadek Kiki Novita MAHAENI; A.A. Ketut JAYAWARSA; Kompiang BAGIADA (Indonesia Strategic Sustainability, 2021)
This study aimed to determine the effect of gender, parental income, and area of origin on financial literacy in the simultaneous and partial use of financial ins titution products and services among active students in the fifth semester of the Faculty of Economics and Business Warmadewa University. The results showed that gender, parents' income, and area of origin had a significant positive effect on financial literacy in the use of products and services of financial institutions. Then partially, gender has a significant positive effect on financial literacy in the use of products and services of financial institutions, while the income of parents and area of origin has no effect on financial literacy in the use of products and services of financial institutions.